2019
DOI: 10.1002/adom.201901002
|View full text |Cite
|
Sign up to set email alerts
|

Strong Plasmon–Exciton Interactions on Nanoantenna Array–Monolayer WS2 Hybrid System

Abstract: Strong plasmon–exciton interactions in monolayer transition‐metal dichalcogenides (TMDs) is emerging as a promising material platform for light emissions, nonlinear optics, and quantum communications, and their realizations require highly localized electric fields parallel to the transition dipole moment of TMD excitons. Here, a systematic study of light–matter interaction in planar dimer nanoantenna of nanoscale gaps coupled with monolayer WS2 is presented, where the effects of the local field enhancement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 64 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…Therefore, it is imperative to use other complementary characterization methods that can provide further insight about the plasmon–exciton coupling mechanism at work. For instance, examples of such methods are photoluminescence in the far‐ and near‐field and/or spectroscopic methods enabling direct or indirect access to the absorption cross‐section . In addition, plasmon–exciton polaritons have also been observed using electron energy‐loss‐spectroscopy; this technique opens enticing perspectives for probing plasmon–exciton interactions at the true nanometer scale.…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is imperative to use other complementary characterization methods that can provide further insight about the plasmon–exciton coupling mechanism at work. For instance, examples of such methods are photoluminescence in the far‐ and near‐field and/or spectroscopic methods enabling direct or indirect access to the absorption cross‐section . In addition, plasmon–exciton polaritons have also been observed using electron energy‐loss‐spectroscopy; this technique opens enticing perspectives for probing plasmon–exciton interactions at the true nanometer scale.…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
“…In addition, plasmon–exciton polaritons have also been observed using electron energy‐loss‐spectroscopy; this technique opens enticing perspectives for probing plasmon–exciton interactions at the true nanometer scale. Furthermore, recent experimental works involving photoluminescence spectroscopy of LSPRs coupled to organic molecules or excitons in TMDCs have reported that most of the spontaneously emitted light originates from the LPB, with very little emission arising from the UPB. Nevertheless, more investigations—e.g., using time‐domain spectroscopies—are needed in order to obtain a deeper understanding of the dynamics in these systems.…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
“…In the first scenario, the gap spacing ( g ) is adjusted from sub‐10 nm (Figure 1c) to sub‐5 nm (Figure 1d). Given that the smallest gap spacing of planar nanostructures based on lift‐off pattern transfer is in the sub‐10 nm range, [ 52 ] it is not possible to achieve sub‐5 nm in taller nanostructures using standard lift‐off method. Our strategy to achieve the sub‐5 nm gap spacing lies in the use of lateral force during electrodeposition to compress the resist structure in the gap region, as illustrated in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Strong coupling is made possible by the local optical density of photonic states (LDOS), which is primarily determined by the spatiotemporal confinement of electromagnetic fields, as characterized by the mode volume V and resonance Q-factor, LDOS α Q/V. Because of their direct band gap and large exciton binding energy, numerous systems integrating TMDs monolayer and plasmonic nanostructures have recently demonstrated robust plasmon–exciton coupling [ 6 , 7 ]. However, since many of the novelties and prospective applications of these monolayer TMDs are based on their excitonic light emission, having a controllable emission in such systems is essential for developing efficient photonic components.…”
Section: Introductionmentioning
confidence: 99%